(3GdLhGH GdfGWb HGdMb Gdjbjf GdTGaj dUOhQ GdeJbjfs - (3GdgGOj Hf EHQGgje Hf Ydj Hf GdeQJVj GdMSjfj Hf GdhRjQ,LeGd GdOjf , GHf GdhRjQ, J (B822 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi CeQ HGdYOd hGdEMSGf , hfgi Yf GdRjZ hGdYOhGf s
(3BNQgG (B:s
(3hGdeSDhd Cf jSdc HfG efgL GdSfI hGdcJGH , hCf jLYd CYeGdfG NGdUI dhLI , heWGHbI dQUGg hcGf JeGe gPG GdLhGH ai GdfUa ef QHjY GdBNQ , SfI JSY hKeGfeGFI s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdChds
(3GdfSNI HgG MhGTs
(3hgh cJGH ai GdQO Ydi LeGd GdOjf Ydi Hf eMeO Hf CHj GdbGSes
(3ai fbVg dbUjOI eMeO Hf EHQGgje ai YbjOJg (B[ (3YbjOI Cgd GdHjJ (B] (3Ydi MhGTjgG JUMjMGJ hJYdjbGJ s
(3hHBNQgG bQGAI SfI (B977 s
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
Keywords: (3Gdabg GdESdGejs